The Study of Phisical Changes in Bireuen Pendopo (Case Study: Pre-Independence, Independence And After Area Expansion) - Cut Azmah Fithri; Mohammad S Arar; Shofia Farhan; Yenny Novianti (International Journal of Engineering, Science and Information Technology, 2022)
Bireuen Regency is an area that has historical buildings from the Dutch colonial era, one of which is the Bireuen Pendopo. It is a cultural heritage building that is more than 70 years old based on the photo archive of Ir. Sukarno with the Bireuen fighter in 1948 and was certified as "The President Sukarno Heritage List". The building has undergone changes, seen from the period of pre-independence (1934–1944), the period of independence (1945–1999), and the period after the area expansion (1999–2021). Pendopo is a cultural heritage building. A study of its physical changes is urgently needed so that the original shape does not change and the material is not entirely replaced. The purpose of this study is to identify the physical changes in the Bireun Pendopo building. The research method used is descriptive qualitative. The physical elements are categorized into minor transformation, major transformation, and full transformation. The study's results found that the Bireun Pendopo building in the pre-independence period (1934-1944) did not have any changes in its physical form. While during the independence period (1945-1998), it underwent a minor physical transformation. In the period after the expansion of Bireun Regency (1999-2020), it underwent a minor physical transformation, a major transformation, and a full transformation. The results of the study that identified the physical changes of the Bireun Pendopo based on three periods showed that most of the changes were carried out in the post-expansion period with major and full transformation categories.